(untitled) (Ustozlar uchun, 2025)
Abstract: The rapid development in the field of Prenatal medicine has led to an increase in the number of various tracheobronchial interventions in the respiratory system organs of fetuses and infants. The study of the laws of organogenesis of the respiratory system makes it possible to better understand the etiopathogenesis of birth defects, and the reasons for the occurrence of structural variants of its structural components. Excellent data on the specifics of organogenesis of the lungs and upper respiratory tract lead to the production and improvement of existing new methods of prevention, diagnosis and treatment of congenital and acquired pathologies in thorocal surgery and pulmonology.